62.3k views
5 votes
What are the transformations on the following
function, f (x) = -2 log4 (x + 5) - 4?

User Piemol
by
5.3k points

1 Answer

3 votes

Answer:

8

Explanation:

= f (x) = -2 log 4 (x + 5) - 4

= 4 (-2 + 5) - 4

= So you do -2 + 5 because they are in ( ) so you do it first so (-2 + 5) = 3

= So now you have 4 (3) - 4

= You do 4 and (3) because when you have a 4 by a ( ) that means you multiply.

= 4 (3) which is the same as 4 × 3 which is 12.

= then you do 12 - 4 which is 8.

= 8 is your answer.

I hope this helps.

User Fentas
by
5.6k points